PERTUMBUHAN DAN HASIl SELADA KERITING (Lactuca sativa L.) PADA DATARAN RENDAH DENGAN PEMBERIAN DOSIS DAN APLIKASI FREKUENSI BOKASHI DAUN LAMTORO - Sri Mulatsih; Sarina Sarina; Miftah Miftah (Jurnal Agroqua: Media Informasi Agronomi dan Budidaya Perairan, 2021)
The potential yield of lettuce cultivation can be increased by fertilization, either in the form of anorganic fertilizers or organic fertilizers. The continuous use of anorganic fertilizers in plant cultivation can have an adverse impact on the environment. Therefore, the use of organic fertilizers in agriculture can be an alternative and reduce the use of anorganic fertilizers among farmers. Lamtoro (Leucaena leucocephala (Lam) dewit) is a type of leguminous plant that has the potential to be used as a raw material for making bokashi fertilizer. The leaves of lamtoro (Leucaena leucocephala (Lam) dewit)i have sufficient nutrient content and are in accordance with SNI standards. This study aims to determine the growth response and the best yield of curly lettuce plants in the lowlands at the dose treatment and application frequency of bokashi leaf fertilizer lamtoro (Leucaena leucocephala (Lam) dewit). This research conducted at Bumi Ayu village Selebar, Bengkulu City from April to May 2021. The research method used a Factorial Completely Randomized Design (CRD) with 3 replications. The first factor (bokashi dose) consisted of 5 levels (D1 : 5 t/ha, D2 : 10 t.ha, D3 : 15 t/ha, D4 : 20 t/ha and D5 : 200 kg/ha). The second factor (F1 : 1 MST, F2 : 2 times, 1 MST and 2 MSetT and F3 : 1 MST, 2 MST and 3 MST). The results showed that the dose of bokashi leaf lamtoro (Leucaena leucocephala (Lam) dewit) of 15 tons/ha gave the best growth and yield as indicated by the variables of plant height, leaf diameter and wet weight of curly lettuce. The dose of 15 t/ha gave the result in the form of fresh weight equivalent to 1,799 t/ha.